Les débuts de la poste à Ahunstic-Cartierville - Poitras, Jean (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Bordeaux; Cartierville; Poste; Sault-au-Récollet

Les premières institutions bancaires de la rue Masson - Gouin, Christiane (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Banque Canadienne nationale; Banque d'Hochelaga; Banque de Montréal; Banques

Marion Nelson Crawford, la partenaire du notable fermier de la Côte-de-la-Visitation - Guilbault, Normand (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Crawford, Alexander

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Montréal, Heart of Indigenous Diplomacy - Arsenault, Mathieu (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Autochtones; Parlement

Dictionnaire historique des gens du livre au Québec - Aubin, Paul; Luneau, Marie-Pier; Vincent, Josée (Les Presses de l'Université de Montréal, 2022)
Keywords: Imprimerie

A very Partisan Press - Bérubé, Harold (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Avenir (L'); La Fontaine, Louis-Hippolyte; Minerve (La); Montreal Gazette; Montreal Herald; Papineau, Louis-Joseph; Partis politiques

Les quartiers de la grande bourgeoisie: le cas du Golden Square Mile à Montréal - Bérubé, Harold (Histoire des villes nord-américaines, 2022)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

At St Anne's Market (1834-1844). All Kinds of Products, All Kinds of Meetings - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Alimentation; Boucherie; Marchands; Marchés; Sainte-Anne (marché)

St Anne's Market. A Long-Awaited Project - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Marchés; Sainte-Anne (marché)

Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie, 2022)
Keywords: Archives; Femmes; Écrivains

Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada - Pothier, Louise; Cecchini, Lisa; Hamilton, Patricia; Knowles, Terry (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2022)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

For Our Collective Heritage. Nothing Is Loss Forever - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché)

St Anne's Market and its Underground Waters. Imagination and Innovation - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Marchés; Sainte-Anne (marché)

Évolution du village de Saint-Jean-Baptiste - Deschambault, Gabriel (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
Keywords: Saint-Jean-Baptiste (village); Villages

L'intendance sociale du capital : philanthropie d'entreprise et hôpitaux généraux montréalais, 1880-1915 - Dubreuil, Anne-Marie (Université du Québec à Montréal, 2022)
Keywords: Hôpital Notre-Dame; Hôpitaux; Montreal General Hospital; Philanthropie; Royal Victoria Hospital

Kingston to Montréal. Inside the Parliamentary Libraries - Gallichan, Gilles (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Parlement

Moving the Seat of Parliament. From Kingston to Montréal - Gallichan, Gilles (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Parlement

A Building Transformed. From Market to Parliament - Gignac, François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Marchés; Parlement; Sainte-Anne (marché)

Discovering Parliament in Montréal - Gignac, François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Parlement

Le collier d'office - Guiard, Jean-Paul (Il était une fois...Montréal-Nord, 2022)
Keywords: Maires; Montréal-Nord

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Behind Strong Palings: Producing Knowledge in the Modern City at Montreal’s Emigrant Sheds, 1832-1852 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Choléra; Épidémies

Les témoins et la justice militaire pendant les Rébellions au Bas-Canada, 1837-1839 - Lafond, François (Université Laval, 2022)
Keywords: Rébellions

« Se soumettre de bon coeur à son mari »: le combat d'une femme face à l'autoritarisme marital - Lamonde, Yvan (Presses de l'Université Laval, 2022)
Keywords: Avocats; Doutre, Joseph; Femmes; Guibord, Joseph; Institut canadien; Mariage; Renaud, Marie-Zoé-Aimée; Trudel, François-Xavier-Anselme; Ultramontains

Soundways Montreal to La Cloche - Laxer, Daniel Robert (Listening to the Fur Trade. Soundways and Music in the British North American Fur Trade, 1760-1840, 2022)
Keywords: Autochtones; Fourrure; Marchands

Rebellion Losses Bill: Mere Pretext or the Real Cause of the Burning of Parliament - Leblanc, Jean-François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Incendies; Parlement; Rébellions; Réformistes; Torys; Émeutes

La Côte-de-Saraguay - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Côtes; Saraguay; Villages

Éclairer et perfectionner l’esprit : l’éducation libérale et le délicat compromis entre raison et foi dans les écoles classiques de langue anglaise au Bas-Canada (1800-1840) - McCutcheon, Shawn (Études d'histoire religieuse, 2022)
Keywords: Langue; Libéralisme

“Perfect Dry Plates for Canada”: Gelatine Dry-Plate Manufacturing in Canada in the Late Nineteenth Century - Perry, Shannon (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine, 2022)
Keywords: Notman, William; Photographie; Publicité

DUPUIS, JOSEPH-NARCISSE (Dictionnaire biographique du Canada, 2022)

L’épopée de la « Petite rivière » devenue un égout patrimonial à Montréal - Pothier, Louise (Les Cahiers des dix, 2022)
Keywords: Musée Pointe-à-Callière; Patrimoine; Égouts

Two Commemorative Pitchers, or the End of an Era. 1846. Repeal of the Corn Laws - Pothier, Louise (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Céréales; Incendies; Marchands; Mouvement annexionniste; Parlement; Prix

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

CULLEN, MAURICE GALBRAITH - Prioul, Didier (Dictionnaire biographique du Canada, 2022)

Aux origines du village de Saint-Jean-Baptiste, 1850-1861 - Robert, Jean-Claude (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
Keywords: Saint-Jean-Baptiste (village); Villages

1844-1849. Montréal, the New Seat of Government - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

1849. To the Parliament House! - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Incendies; Parlement; Torys; Émeutes

In Response to the Unrest, Petitions in Support of the Queen Poured in. Denouncing the Tories to Save the Empire - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Incendies; Mouvement annexionniste; Parlement; Réformistes; Torys; Émeutes

Montréal, Hospitable Capital City - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Hôtellerie; Marchés

After the Fire Comes the Investigation. Citizens Give Testimony - Roy, Alain; Horner, Dan (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Incendies; Parlement; Torys; Émeutes

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Chemins de fer; Paysages

Sir Hormisdas Laporte: Homme d'affaires et maire de Montréal (1850-1934) - Saint-Pierre, Marjolaine (Septentrion, 2022)
Keywords: Maires; Philanthropie

Photography: Science, Technology, and Practice in Nineteenth-Century Canada - Schwartz, Joan M. (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine, 2022)
Keywords: Astronomie; Géologie; Notman, William; Photographie

Histoire du site des moulins du Sault-au-Récollet - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Meunerie; Patrimoine; Sault-au-Récollet

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

Les élections au temps des patriotes : conflits, violence et politisation en contexte électoral (1820-1834) - Théberge, Samuel (Université du Québec à Montréal, 2022)
Keywords: Minerve (La); Montreal Gazette; Montreal Herald; Élections

BLANCHARD, JULIE-MARGUERITE-LIA - Thifault, Marie-Claude (Dictionnaire biographique du Canada, 2022)

BÉÏQUE, FRÉDÉRIC-LIGORI - Vallières, Marc (Dictionnaire biographique du Canada, 2022)